PENGARUH KEGIATAN PROMOSI TERHADAP PREFERENSI MAHASISWA DALAM MEMILIH UNIVERSITAS DEHASEN BENGKULU - Fera Inda Sari (Professional: Jurnal Komunikasi dan Administrasi Publik, 2017)
This study aimed to analyze the effect of promotional activities on student preferences in choosing Dehasen University of Bengkulu on the assumption that a person chooses for their factors of rational choice inside. Variable influence of promotional activities are : X1 (advertising), X2 (personal selling), X3 (Publicity), the control variables are : Z1 (selective buying motives), Z2 (patronage buying motives), Z3 (primary buying motives), and variables affected Y (Student preferences). The sample in this research were 245 peoples who are students at the University of Bengkulu Dehasen force from 2015 to 2016. The results of the study found that the ads are not able to influence the primary buying motives University Students Dehasen Bengkulu for prospective students consider one of the basic needs is education, so basically students who feel that education is a basic requirement will not see advertising as a reference, but the impact of fulfillment the study is due to have a proper education, students will have the ability in a variety of academic fields so that students will get a decent job and of the rewards of decent work in addition to the basic needs of education students will be able to be fulfilled optimum. Variable personal selling and publicity can influence selective buying motives, patronages buying motives, and the primary buying motives, but patronage buying motives has no influence on the preference of the student so that it can be concluded that personal selling and publicity will be able to influence the preferences of students by influencing selective buying motives and Pimary buying motives first. Keywords : Promotion Activities, The Rational Choice, Preference